Przestrzeganie praw nieletnich na terenie młodzieżowych ośrodków wychowawczych - Kamiński, Arkadiusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The socio-political transformations that began in Poland in 1989 have also contributed to the changes in the functioning of Youth Resocialization Centers. During that period the facilities became friendlier to the persons detained in the centers. The metamorphosis of these institu-tions has largely been forced by ratification of international agreements, which have influ-enced the changes in national legislation. In addition, established audit institutions resulted in the need to adapt to the prevailing practices. Gradual transformations ultimately contributed to the increase of the sense of security on the part of the young people placed in the institu-tions of youth resocialization.
Keywords: umowy międzynarodowe; prawo; nieletni; placówki resocjalizacyjne; zmiany polityczne